PENYAJIAN DATA TEKNIS SUMUR RESAPAN BERBASIS SISTEM INFORMASI GEOGRAFIS (SIG) DALAM UPAYA MENDUKUNG KEBIJAKAN PENGELOLAAN SUMBER DAYA AIR YANG BERKELANJUTAN - Joleha Joleha; Bochari Bochari; Alfian Malik; Suprasman Suprasman; Elianora Elianora; Safridatul Audah (Pelantar Press, 2024)
The Population growth and development in an area lead to increased water demand and reduced use of green land. These changes can cause environmental degradation, decrease in environmental quality and existing water resources. Therefore, wise and sustainable development is needed for society. In this case the Government of Pekanbaru City has included a policy on Water Resources and Infiltration Wells in the Regional Regulation (PERDA No. 10 of 2006). One of the main objectives of implementing the PERDA is to prevent stagnation of water during the rainy season which can be detrimental to the community, especially in residential areas and other buildings. However, some researchers has stated the reality in the field that the implementation of this PERDA is not going well. Technical provisions for the use of infiltration wells are water level elevation and soil permeability which must meet the requirements. Therefore, this study aims to measure the elevation of the groundwater table, test the permeability of the soil and present the test values and measurements on a spatial map Therefore, this study aims to measure the elevation of the groundwater table, test the permeability of the soil and present the test and measurement values into a spatial map based on a geographic information system (GIS). This spatial map depicts the coordinates of sampling points that provide information on permeability values and groundwater levels, as well as recommendations for making infiltration wells at each sample point that meet the requirements. Thus, this spatial map can help residents or the government to obtain information on which locations are recommended for infiltration wells, because not all locations can be used.